Prospects in Folate Receptor-Targeted Radionuclide Therapy - Müller, Cristina; Schibli, Roger (Frontiers in Oncology, 2013)
Targeted radionuclide therapy is based on systemic application of particle-emitting radiopharmaceuticals which are directed towards a specific tumor-associated target. Accumulation of the radiopharmaceutical in targeted cancer cells results in high doses of absorbed radiation energy whereas toxicity to non-targeted healthy tissue is limited. This strategy has found widespread application in the palliative treatment of neuroendocrine tumors using somatostatin-based radiopeptides. The folate receptor (FR) has been identified as a target associated with a variety of frequent tumor types (e.g. ovarian, lung, brain, renal and colorectal cancer). In healthy organs and tissue FR-expression is restricted to only a few sites such as for instance the kidneys. This demonstrates why FR-targeting is an attractive strategy for the development of new therapy concepts. Due to its high FR-binding affinity (KD < 10-9 M) the vitamin folic acid has emerged as an almost ideal targeting agent. Therefore, a variety of folic acid radioconjugates for nuclear imaging have been developed. However, in spite of the large number of cancer patients who could benefit of a folate-based radionuclide therapy, a therapeutic concept with folate radioconjugates has not yet been envisaged for clinical application. The reason is the generally high accumulation of folate radioconjugates in the kidneys where emission of particle-radiation may result in damage to the renal tissue. Therefore, the design of more sophisticated folate radioconjugates providing improved tissue distribution profiles are needed. This review article summarizes recent developments with regard to a therapeutic application of folate radioconjugates. A new construct of a folate radioconjugate and an application protocol which makes use of a pharmacological interaction allowed the first preclinical therapy experiments with radiofolates. These results raise hope for future application of such new concepts also in the clinic.